Primary cutaneous B-cell lymphomas. Current concepts. I - M Santucci; N Pimpinelli (Haematologica, 2004)
BACKGROUND: Primary cutaneous B-cell lymphoma (pCBCL) has only recently been recognized as a distinct clinicopathologic entity. This entity represents a wide spectrum of lymphoproliferative disorders that must be separated from non-Hodgkin’s B-cell lymphomas secondarily involving the skin and cutaneous B-cell pseudolymphomas. They are defined as B-cell lymphomas originating in the skin, with no evidence of extracutaneous disease at presentation, as assessed by adequate staging procedures. INFORMATION SOURCES: With the advent of improved immunophenotyping and immunogenotyping, increasing numbers of pCBCL cases are being diagnosed. However, there is still confusion regarding the classification, treatment, and prognosis of these patients. The aim of this paper is to provide the clinician with a concise summary of the diagnosis, course, and treatment of pCBCL. Currently, the European Organization for Research and Treatment of Cancer classification is the most adequate classification scheme, identifying the subtypes of pCBCL by clinical behavior and histopathologic findings, and allowing a better management of the patients. STATE OF THE ART: Based on this classification, the most common subtypes of pCBCL are follicular center cell lymphoma and marginal zone B-cell lymphoma, indolent lymphomas with an excellent prognosis (>95% 5-year survival rate in our series). Although local cutaneous recurrences are observed in about 25% of patients, dissemination to internal organs is rare. A less common, specific subtype - the so-called large B-cell lymphoma of the leg(s) - generally has a poorer prognosis, with a 5-year survival rate of approximately 60%. PERSPECTIVES: As a rule, pCBCL is highly responsive to radiation therapy, which should be considered the treatment of choice. Polychemotherapy should be restricted to patients with involvement of several noncontiguous anatomic sites, those refractory or plurirelapsed after radiotherapy, or those with extracutaneous spread.